A STUDY ON STUDENTS’ ABILITY IN DETERMINING DERIVATIONAL MORPHEMES AND INFLECTIONAL MORPHEMES - Aziva Iftinah; Novitri; Dahnilsyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to investigate the students’ ability in identifying derivational and inflectional morphemes at the University of Riau’s English Study Program. The subjects of this study are fifth-semester students enrolled in morphology courses during the academic year 2025/2026. This study employs a quantitative descriptive design, utilizing tests composed of multiple-choice and fill-in-the-blank items to assess students’ recognition and understanding of morphemes within sentences. The findings show that students’ ability in identifying derivational morphemes is approximately 54%, while their proficiency in inflectional morphemes is higher at around 64%. The results indicate that students perform better in recognizing grammatical inflectional markers than lexical derivational forms, highlighting the need for more focused instruction on derivational morphology. The study contributes to language education by emphasizing the importance of morphological awareness in enhancing vocabulary, reading, and writing skills among EFL learners. These findings can inform educators to improve pedagogical strategies in teaching morphology, supporting the development of students’ linguistic competence in English. This research provides valuable insights for further studies in morphology and vocabulary development in EFL contexts.